Water vapor sorption performance of ACF-CaCl2 and silica gel-CaCl2 composite adsorbents. (5th May 2016) - Wang, J.Y.; Wang, R.Z.; Wang, L.W.
Highlights: A novel composite adsorbent for air-to-water system is proposed. The water uptake performance of ACF-CaCl2 is three times more than silica gel-CaCl2 . SEM, ICP and ASAP2020 are adopted to analyze the micro characteristics of compounds. Abstract: A novel composite adsorbent of host matrix of CaCl2 was developed to increase mass transfer area and enhance adsorption performance for air-to-water system under hot and humid conditions. The host matrix is activated carbon fiber felts (ACF FELT) fabricated by viscose-based fibers. Scanning electron microscope (SEM) and Micromeritics ASAP2020 were adopted to observe the micro characteristics of matrix. Inductive coupled plasma emission spectrometer (ICP) was used to test the quality of impregnation and water crystallization carried by calcium chloride in synthesis. The preparation processes, pore structures, quantities of crystallization water of calcium chloride and impregnated salt, as well as the non-equilibrium adsorption performances were studied, and the results were compared with the composite adsorbents with SC matrix. Research shows that ACF is more suitable as the matrix of composite adsorbents, and ACF30 has the best sorption performance of water uptake 1.7 g/g, which is three times more than silica gel-CaCl2 . Furthermore, ACF compound can be retested without rupture or carryover. Coefficient of adsorption rate of water uptake was obtained using Linear Driving Force model.